An Empirical Comparison of Default Swap Pricing Models - Patrick Houweling; Ton Vorst (Tinbergen Institute, 2002)
In this paper we compare market prices of credit default swaps with model prices. We showthat a simple reduced form model with a constant recovery rate outperforms the market practice ofdirectly comparing bonds' credit spreads to default swap premiums. We find that the model workswell for investment grade credit default swaps, but only if we use swap or repo rates as proxy fordefault-free interest rates. This indicates that the government curve is no longer seen as thereference default-free curve. We also show that the model is insensitive to the value of theassumed recovery rate.
Keywords: 330; Swap; Derivat; Zinsstruktur; Optionspreistheorie; Swap; Derivat; Optionspreistheorie; Theorie